Development of a Novel Lateral Flow Biosensor Combined With Aptamer-Based Isolation: Application for Rapid Detection of Grouper Nervous Necrosis Virus - Liu, Jiaxin; Qin, Qiwei; Zhang, Xinyue; Li, Chen; Yu, Yepin; Huang, Xiaohong; Mukama, Omar; Zeng, Lingwen; Wang, Shaowen (Frontiers in Microbiology, 2020)
Nervous necrosis virus (NNV) has infected more than 50 fish species worldwide, and has caused serious economic losses in the aquaculture industries. However, there is no effective antiviral therapy. The development of a rapid and accurate point-of-care diagnostic method for the prevention and control of NNV infection is urgently required. Commonly used methods for NNV detection include the cell culture-based assay, antibody-based assay and polymerase chain reaction (PCR)-based assay. However, these methods have disadvantages as they are time-consuming and complex. In the present study, we developed a simple and sensitive aptamer-based lateral flow biosensor (LFB) method for the rapid detection of red-spotted grouper nervous necrosis virus (RGNNV). An aptamer is a single-stranded nucleotide, which can specifically bind to the target and has many advantages. Based on a previously selected aptamer, which specifically bound to the coat protein of RGNNV (RGNNV-CP), two modified aptamers were used in this study. One aptamer was used for magnetic bead enrichment and the other was used for isothermal strand displacement amplification (SDA). After amplification, the product was further tested by the LFB, and the detection results were observed by the naked eye within 5 min with high specificity and sensitivity. The LFB method could detect RGNNV-CP protein as low as 5 ng/mL or 5×103 RGNNV-infected GB (grouper brain) cells. Overall, it is the first application of a LFB combined with aptamer in the rapid diagnosis of virus from aquatic animals，which provides a new option for virus detection in aquaculture.